N-Acetylcysteine and Other Sulfur-Donors as a Preventative and Adjunct Therapy for COVID-19 - Heidi N du Preez; Colleen Aldous; Hendrik G Kruger; Lin Johnson (Advances in Pharmacological and Pharmaceutical Sciences)
The airway epithelial glycocalyx plays an important role in preventing severe acute respiratory syndrome coronavirus 2 entry into the epithelial cells, while the endothelial glycocalyx contributes to vascular permeability and tone, as well as modulating immune, inflammatory, and coagulation responses. With ample evidence in the scientific literature that coronavirus disease 2019 (COVID-19) is related to epithelial and endothelial dysfunction, preserving the glycocalyx should be the main focus of any COVID-19 treatment protocol. The most studied functional unit of the glycocalyx is the glycosaminoglycan heparan sulfate, where the degree and position of the sulfate groups determine the biological activity. N-acetylcysteine (NAC) and other sulfur donors contribute to the inorganic sulfate pool, the rate-limiting molecule in sulfation. NAC is not only a precursor to glutathione but also converts to hydrogen sulfide, inorganic sulfate, taurine, Coenzyme A, and albumin. By optimising inorganic sulfate availability, and therefore sulfation, it is proposed that COVID-19 can be prevented or at least most of the symptoms attenuated. A comprehensive COVID-19 treatment protocol is needed to preserve the glycocalyx in both the prevention and treatment of COVID-19. The use of NAC at a dosage of 600 mg bid for the prevention of COVID-19 is proposed, but a higher dosage of NAC (1200 mg bid) should be administered upon the first onset of symptoms. In the severe to critically ill, it is advised that IV NAC should be administered immediately upon hospital admission, and in the late stage of the disease, IV sodium thiosulfate should be considered. Doxycycline as a protease inhibitor will prevent shedding and further degradation of the glycocalyx.